1999
DOI: 10.1038/sj.ejcn.1600734
|View full text |Cite
|
Sign up to set email alerts
|

Impact of zinc supplementation on subsequent growth and morbidity in Bangladeshi children with acute diarrhoea

Abstract: Objective: To assess the impact of zinc supplementation during acute diarrhoea on subsequent growth and morbidity in malnourished young children. Design: Double blind randomized controlled clinical trial Setting: International Centre for Diarrhoeal Disease Research, Bangladesh. Subjects: Sixty-®ve children aged 3 ± 24 months with acute diarrhoea for less than 3 d. Intervention: Either elemental zinc (20 mgad) in a multivitamin syrup or multivitamin syrup alone divided in three divided daily doses for a period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 37 publications
3
64
0
1
Order By: Relevance
“…In this study, zinc supplementation reduced the number of diarrhoeal episodes during the 6-month follow-up, which corroborates the findings of our earlier studies on short-term zinc supplementation during acute diarrhoea (Roy et al, 1999) and persistent diarrhoea (The Zinc Investigators' Collaborative Group, 2000; Roy et al, 2007). This effect could have resulted from immunological and nutritional benefits of zinc supplementation, better mucosal repair and growth (Alam et al, 1994).…”
Section: Table 1csupporting
confidence: 80%
See 2 more Smart Citations
“…In this study, zinc supplementation reduced the number of diarrhoeal episodes during the 6-month follow-up, which corroborates the findings of our earlier studies on short-term zinc supplementation during acute diarrhoea (Roy et al, 1999) and persistent diarrhoea (The Zinc Investigators' Collaborative Group, 2000; Roy et al, 2007). This effect could have resulted from immunological and nutritional benefits of zinc supplementation, better mucosal repair and growth (Alam et al, 1994).…”
Section: Table 1csupporting
confidence: 80%
“…However, in our study the beneficial effect of zinc on growth, as observed during hospitalization, was not sustained during the follow-up period. This could result from one or more of the following: relatively shorter duration of zinc supplementation to overcome the strong catabolic effects of shigellosis, which was not adequate for sustained growth thereafter, but reported earlier (Roy et al, 1999) and significant enteric protein and micronutrient loss in stool during acute-stage diarrhoea (Castillo-Duran et al, 1988;Bennish et al, 1993).…”
Section: Table 1cmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence to show preventive and therapeutic effects of zinc supplementation on various childhood morbidities (18,(25)(26)(27)(28)(29)(30). Our morbidity-related results showed that children with zinc deficiency were at a higher risk of morbidities compared to zinc-sufficient children.…”
Section: Discussionsupporting
confidence: 50%
“…There are now a number of studies showing that Zn supplementation decreases the incidence of childhood diarrhoea (Ninh et al 1996;Sazawal et al 1996Sazawal et al , 1998Rosado et al 1997;Roy et al 1997Roy et al , 1999Ruel et al 1997) and respiratory illness (Ninh et al 1996;Sazawal et al 1998;Roy et al 1999). However, some studies fail to show bene®t of Zn supplementation in respiratory disease (Bates et al 1993;Rosada et al 1997;Ruel et al 1997;Lira et al 1998).…”
Section: Zincmentioning
confidence: 99%